Analisis Perkembangan Anak Usia SD Kelas 3 di Laut Dendang Kecamatan Percut Sei Tuan - Ramadhan Lubis; Dinah Nadhifah; Alfiah Hairani; Yuli Deliyanti; Nepri Handayani Siregar (Journal on Education, 2025)
This study aims to analyze the physical, psychomotor, emotional, social, cognitive, moral and spiritual development of Muhammad Nur Ihsan, a grade 3 primary school child, based on interviews with his mother Ismaya. The results showed that Ihsan had good development in physical and psychomotor aspects, such as independence in maintaining personal hygiene and good drawing skills, although there were challenges in sleep order and handwriting. Emotionally, Ihsan is able to express his feelings although sometimes his emotions are difficult to control, such as when angry. Socially, Ihsan gets along easily with his friends but needs to develop more empathy towards his younger siblings. His cognition is developing with great curiosity and the ability to complete tasks independently, although he tends to delay difficult tasks. Morally and spiritually, Ihsan is diligent in praying and reciting the Quran, although his emotional management still needs to be improved. Overall, Ihsan shows good development with some areas that require more attention to optimize his potential.